2002
DOI: 10.1007/s11882-002-0020-3
|View full text |Cite
|
Sign up to set email alerts
|

Thoughts on the pathophysiology of nonallergic rhinitis

Abstract: Nonallergic noninfectious rhinitis is a diagnosis by exclusion, meaning that a number of poorly defined nasal conditions that have in common allergy and infection as a cause of the rhinitis have been excluded. The etiology of some subgroups of nonallergic noninfectious rhinitis, like nonallergic rhinitis with eosinophilia (NARES) and drug-induced rhinitis, are quite well defined, but in the majority of the patients, the etiology and pathophysiology are unknown. These patients are classified as idiopathic rhini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 58 publications
0
54
0
1
Order By: Relevance
“…Persistent nonallergic rhinitis with eosinophilia is a heterogeneous syndrome consisting of at least two subgroups: NARES and aspirin hypersensitivity (30).…”
Section: Nares and Eosinophilic Rhinitismentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent nonallergic rhinitis with eosinophilia is a heterogeneous syndrome consisting of at least two subgroups: NARES and aspirin hypersensitivity (30).…”
Section: Nares and Eosinophilic Rhinitismentioning
confidence: 99%
“…Several nonallergic conditions can cause similar symptoms: infections, hormonal imbalance, physical agents, anatomical anomalies and the use of certain drugs (30). Rhinitis is therefore classified as shown in Table 2 (1).…”
Section: Introductionmentioning
confidence: 99%
“…Several nonallergic conditions can cause similar symptoms: infections, hormonal imbalance, physical and chemical agents, anatomical anomalies and the use of certain drugs (3). However, many patients have symptoms that mimick allergic rhinitis, with no definite causal factor and with a lack of demonstrated IgE-mediated allergy by skin prick tests and allergen-specific serum IgE (4).…”
Section: Magnitude Of the Problemmentioning
confidence: 99%
“…Indeed, some authors have suggested that there is a large subgroup of patients with symptomatic NAR in the absence of any inflammatory changes in the nasal mucosa. In these patients, it is not possible to identify an inflammatory cell infiltrate such us in hormonal rhinitis, damage to sympathetic nerves as in Horner's syndrome or overuse of topical-adrenergic agonists/ nasal decongestants ("rhinitis medicamentosa") (22) . On the other hand, several authors have demonstrated that most patients with NAR have some degree of inflammation suggesting that nasal cytological evaluation may aid in identifying forms of NAR in which inflammation is involved and in classifying this latter according to the inflammatory cell type (3) .…”
Section: Introductionmentioning
confidence: 99%